2019
DOI: 10.3991/ijim.v13i09.10918
|View full text |Cite
|
Sign up to set email alerts
|

Usability Evaluation of SMS-Based System: Basis for Systems Development

Abstract: The objective of the study is to evaluate the usability of SMS-Based Auto-Reply Inquiry System for Grades and Accounts. This descriptive study used a three-part questionnaire which was administered by the researcher. The usability questionnaire adapted from the USE Questionnaire used a 5-point scale composed of 30 statements. Convenience sampling was used choosing the respondents from the total population of 149 students of the CICS during the second semester of school year 2018-2019. A total of 45 questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
2
0
1
Order By: Relevance
“…In other words, the influence of technical support and course design on promoting continuance intention of using e-training can be strengthen if the e-training program perceived as useful by the participants [26][28].This result showed that perceived usefulness has important influence in both models i.e. direct or indirect effect model and supported by many previous studies on online learning [19][20][21][22][23][24][25] that perceived usefulness of e-learning product has significant role in influencing the willingness of users to continue using the product. Besides having a good technical support and well designed, the online platform for learning as well as training must perceived as useful by the participants in motivating them to continue using it or other platforms like it.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In other words, the influence of technical support and course design on promoting continuance intention of using e-training can be strengthen if the e-training program perceived as useful by the participants [26][28].This result showed that perceived usefulness has important influence in both models i.e. direct or indirect effect model and supported by many previous studies on online learning [19][20][21][22][23][24][25] that perceived usefulness of e-learning product has significant role in influencing the willingness of users to continue using the product. Besides having a good technical support and well designed, the online platform for learning as well as training must perceived as useful by the participants in motivating them to continue using it or other platforms like it.…”
Section: Discussionsupporting
confidence: 70%
“…Learners have always been identified as having a useful and enjoyable experience if the online platform is user-friendly [23]. In addition, the perceived usefulness has been identified as a significant factor in predicting the continuance intention of using an online learning platform, either amongst school or university learners or employees of the organization [3][16][21][24] [25]. The results of previous studies have contributed to the understanding of the aspects that motivate learners to continue use e-learning.…”
Section: E-npqel In Leadership Preparatory Training Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Sistem yang dikembangkan dalam penelitian ini yaitu Sistem Informasi Adminitrasi Keuangan berbasis Website. Sistem tersebut dalam bentuk web yang dapat diakses melalui link dimana terdapat beberapa menu dan fitur yang mendukung pengolahan data (Maggay, 2019;Nuanmeesri, 2020).…”
Section: Pendahuluanunclassified